2014
DOI: 10.1111/ejh.12309
|View full text |Cite
|
Sign up to set email alerts
|

The bone marrow hematopoietic microenvironment is impaired in iron‐overloaded mice

Abstract: Iron-overloaded (IO) mice did not show significant defects in the hematopoietic data of the peripheral blood. Myeloid progenitor cells in the bone marrow were increased in IO mice, but the number and function of the erythroid progenitors and hematopoietic stem cells were not significantly affected. However, bone marrow transplantation from normal donors to IO recipients showed delayed hematopoietic reconstitution, which indicates that excess iron impacts the hematopoietic microenvironment negatively. Microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…Iron overload also caused stromal dysfunction in a mouse model [12]. BM transplantation from normal donor mice to IOL recipients resulted in delayed hematopoietic reconstitution, indicating that excess iron disturbed the hematopoietic microenvironment.…”
Section: Iron Overload and Bone Marrow Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…Iron overload also caused stromal dysfunction in a mouse model [12]. BM transplantation from normal donor mice to IOL recipients resulted in delayed hematopoietic reconstitution, indicating that excess iron disturbed the hematopoietic microenvironment.…”
Section: Iron Overload and Bone Marrow Functionmentioning
confidence: 98%
“…Figure 3 illustrates where IOL may have an aggravating effect on MDS pathophysiology. Experimental evidence indicates that IOL contributes to stromal dysfunction [12,13] and exacerbates genomic instability, thereby hastening clonal evolution towards leukemia.…”
Section: Iron Overload and Bone Marrow Functionmentioning
confidence: 99%
“…Erythroid colony assays were significantly lower in patients with a ferritin > 2.500 ng/ml than in patients with normal ferritin levels [4]. Erythropoietin and thrombopoietin levels were also suppressed, and increased oxidative stress in the bone marrow was observed [18,19]. Another study in transfusion-dependent MDS patients suggested that oxidative stress due to iron overload could cause DNA damage and, therefore, contribute to the MDS development [20].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of erythropoietin and thrombopoietin were significantly low in iron-overloaded mice compared to the normal group. The authors concluded that excess iron disrupts the hematopoietic microenvironment [19]. Zhang et al evaluated the effect of iron overload on the bone marrow microenvironment in mice and found that chemokine stromal cell-derived factor-1, stem cell factor-1, and vascular endothelial growth factor-1 expressions were decreased.…”
Section: Iron Homeostasis and The Mechanisms Of Iron Overloadmentioning
confidence: 99%